Antibody Response Against Sheep Red Blood Cells in Lines Congenic for Major Histocompatibility (B) Complex Recombinants - Schulten, E.S.; Taylor, Jr., R.L.; Yates, L.M. (International Journal of Poultry Science, 2007)
Six congenic lines containing B complex recombinants R1 = B-F/B-L24, B-G23; R2 = B-F/B-L2, B-G23; R3 = B-F/B-L2, B-G23; R4 = B-F/B-L2, B-G23; R5 = B-F/B-L21, B-G19; and R6R6 = B-F/B-L21, B-G23 were tested individually for antibody response against SRBC. R2, R3 and R4 arose from independent recombination events but are serologically identical. Each B complex recombinant was crossed to inbred Line UCD 003 (B17B17). After ten backcross generations to the inbred line, B complex heterozyogtes were mated to produce recombinant homozygous lines having 99.9% background gene uniformity. Birds of each line were injected intravenously with 1 mL of 2.5% SRBC at four and 11 weeks of age to induce primary and secondary antibody responses, respectively. Blood samples were collected 7 days post-injection. Microtiter methods were used to assay total anti-SRBC and mercaptoethanol-resistant (MER) serum antibody. All antibody titers were evaluated by least squares ANOVA with hatch and B recombinant genotype as main effects. Fisher`s protected LSD was used to evaluate significant means. Genotypes R5R5 and R6R6 had significantly higher primary total antibody titer to SRBC compared with R1R1, R2R2, R3R3 and R4R4. Both R5 and R6 have BF21, a haplotype known for high antibody response to SRBC. Primary MER antibody response did not differ significantly among the genotypes. The total and ME-resistant secondary antibody titers of R5R5 chickens were significantly higher than the other five recombinants. These results indicate that congenic lines carrying six B complex recombinants differ in their primary and secondary antibody responses to SRBC.